2005
DOI: 10.1002/cb.22
|View full text |Cite
|
Sign up to set email alerts
|

Opinion leadership in a computer-mediated environment

Abstract: This paper investigates the characteristics of opinion leaders within the computer-mediated environment, analyses the differences between online opinion leaders and online non-leaders and examines the implications of opinion leadership theory for e-commerce. This study finds that opinion leaders in computer-mediated environments possess significantly higher levels of enduring involvement, innovativeness, exploratory behaviour and self-perceived knowledge than non-leaders. Online opinion leaders also possess gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
139
0
17

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 217 publications
(162 citation statements)
references
References 35 publications
6
139
0
17
Order By: Relevance
“…Previous studies have found the way individuals learn about products can influence their levels of product involvement and purchase intentions as much as the products themselves (Chaney, 200 I;Lyons & Henderson, 2005). Linkages like receiving favorable product information from a trusted friend can have a positive effect on product involvement and purchase intentions (Lyons & Henderson, 2005).…”
Section: What Is the Effect Of Linkage Type On The Dissemination Of Imentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have found the way individuals learn about products can influence their levels of product involvement and purchase intentions as much as the products themselves (Chaney, 200 I;Lyons & Henderson, 2005). Linkages like receiving favorable product information from a trusted friend can have a positive effect on product involvement and purchase intentions (Lyons & Henderson, 2005).…”
Section: What Is the Effect Of Linkage Type On The Dissemination Of Imentioning
confidence: 99%
“…Linkage studies have often explored linkage types separately, studying the effects of a single communications channel like word-of-mouth (Lyons & Henderson, 2005) or web portals (Van Baalen, Bloemhof-Ruwaard, & Van Heck, 2005). The current study combined the linkage types to assess their comparative effectiveness in the dissemination of innovations.…”
Section: Study Significancementioning
confidence: 99%
See 3 more Smart Citations